Confucianism and spiritual traditions in modern China and beyond - Yang, Fenggang; Tamney, Joseph B. (Religion in Chinese societies, 2012)
Confucianism is reviving in China and spreading in America. This multidisciplinary volume includes philosophical and theological articulations of Confucianism and other spiritual traditions for the modern and globalizing world, and empirical studies of and analytical reflections on Confucianism and other traditions in Chinese societies by historians, sociologists, and anthropologists